Contraceptive knowledge, attitudes, and use among women visiting primary healthcare centers in Abu Dhabi Island - Taheri, Sumaiya; Sereidi, Amal Al; Mamari, Shammah Al; Darwish, Ebtihal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study assessed contraceptive knowledge, attitudes, and use among women of reproductive age in Abu Dhabi Island. Methods: A cross-sectional study was conducted in primary healthcare centers Al Bateen and Al Rawda in Abu Dhabi Island. Participants were women (N = 384; aged 18-54 years) who were married, widowed, divorced, or sexually active. Using a structured questionnaire, we examined their socio-demographic characteristics and their contraceptive knowledge, attitudes, and use. Results: A total of 44.8% of the women were aged 30-39 years, 98.4% had university education and above, 56.7% were employed, and 69.4% had an adequate family income. Only 23.7% possessed good knowledge about contraceptive methods (e.g., indications/contraindications, side effects, and benefits). Further, 72.1% had used contraception before, while 48.3% were current users. The most commonly used methods were natural methods (63.6%), followed by condoms (35.6%), oral contraceptive pills (34%), and intrauterine devices (33.7%). Interestingly, only 4.6% held a negative attitude toward contraception, while 53.5% were in favor of using contraceptives. Family income and employment status were significantly related to contraceptive knowledge (P = 0.005 and .013, respectively). Number of children, children’s sex, and years of marriage were significantly related to contraception use (P <0.001, <0.001, and 0.008 respectively). Conclusions: Despite poor knowledge about contraception use, most women held favorable attitudes toward using them. About half the women were current contraception users, with natural methods being the most commonly practiced.